The efficacy of applied re warm up protocols in different team sports: a systematic review - Koutsouridis, C.; Galazoulas, C.; Manou, V.; Stavropoulos, N. (Journal of Physical Education and Sport, 2023)
Problem Statement: Passive half-time rest for athletes in team sports could subsequently lead to performance decrements and increased risk of injury. Several studies have shown that active re-warm-up (RWU) protocols could attenuate performance decrements due to passive rest. Purpose: This systematic review aimed to critically analyze the effects of RWU protocols in relation to the team sport in which they were evaluated. Methods: The research was conducted using four electronic databases (the Web of Science, Scopus, Google Scholar and SPORTDiscus), following the PRISMA guidelines and PICO strategy. Only original articles that evaluated the acute effects of RWU protocols were included in the study. On the contrary, RWU protocols that involved exclusively passive strategies were excluded. Results: Out of the 752 relevant studies identified, only 17 met our criteria. The main outcomes were grouped and evaluated in the four different sports: football, team sports, rugby and basketball. The results indicated that there was no consensus on a gold standard protocol that could attenuate most of performance losses provoked by passive rest. All active methods, except for the eccentric exercises that have been shown to be harmful, had beneficial effects on athletic performance compared with passive rest. Conclusions: Athletes should enter game prepared for optimal performance, without the need for a transitional phase to regain the warm-up benefits. Therefore, coaches should establish a short RWU protocol, right before commencing a sport activity, including either intense exercises or sport specific movements, to counteract the negative impact of passive rest on subsequent performance in team sports.